A risk assessment framework for seed degeneration: Informing an integrated seed health strategy for vegetatively-propagated crops - Thomas-Sharma, Sara; Andrade-Piedra, J.L.; Carvajal-Yepes, Mónica; Hernández Nopsa, J.F.; Jeger, Michael; Jones, Roger; Kromann, P.; Legg, James P.; Yuen, Jonathan; Forbes, G.; Garrett, K.A. (Scientific Societies, 2017)
Pathogen buildup in vegetative planting material, termed seed degeneration, is a major problem in many low-income countries. When smallholder farmers use seed produced on-farm or acquired outside certified programs, it is often infected. We introduce a risk assessment framework for seed degeneration, evaluating the relative performance of individual and combined components of an integrated seed health strategy. The frequency distribution of management performance outcomes was evaluated for models incorporating biological and environmental heterogeneity, with the following results. (1) On-farm seed selection can perform as well as certified seed, if the rate of success in selecting healthy plants for seed production is high; (2) when choosing among within-season management strategies, external inoculum can determine the relative usefulness of ‘incidence-altering management’ (affecting the proportion of diseased plants/seeds) and ‘rate-altering management’ (affecting the rate of disease transmission in the field); (3) under severe disease scenarios, where it is difficult to implement management components at high levels of effectiveness, combining management components can be synergistic and keep seed degeneration below a threshold; (4) combining management components can also close the yield gap between average and worst-case scenarios. We also illustrate the potential for expert elicitation to provide parameter estimates when empirical data are unavailable.[Formula: see text] Copyright © 2017 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license .